Biological control of Lasiodiplodia theobromae and Fomitopsis meliae causing the regressive death of citrus - Polanco-Florián, Laura Glenys; Alvarado-Gómez, Omar Guadalupe; Olivares-Sáenz, Emilio; González-Garza, Ramiro; Pérez-González, Orquídea (Revista Mexicana de Ciencias Agrícolas, 2020)
The research was carried out in the state of Nuevo León, Mexico, during 2018, with the aim of isolating and identifying strains of soil microorganisms and evaluating their antagonistic capacity in vitro against citrus pathogens Lasiodiplodia theobromae and Fomitopsis meliae. For the isolation of the microorganisms, 17 rhizosphere samplings were carried out in different locations and types of vegetation; the samples were heat treated and spread by extension in the potato dextrose agar culture medium added with 0.3% yeast extract and 0.3% malt extract (PDLMA). The isolates obtained were preliminarily evaluated by observation and growth comparison. Of 70 isolates, 15 presented antagonistic activity, which showed inhibition percentages of 39-91%. The actinomycete strains M4 R and M1-101, and the fungus M104 (Penicillium citrinum) caused 84,91 and 85% inhibition respectively against L. theobromae and 83, 91 and 91% respectively against F. meliae. Isolation of bacteria was achieved, actinomycetes and fungi from the soil capable of inhibiting the growth of L. theobromae and F. meliae fungi causing regressive citrus death.
Keywords: Fomitopsis meliae; Lasiodiplodia theobromae; antagonism; inhibition